SISTEM ANTRIAN PADA PELAYANAN CUSTOMER SERVICE PT. BANK X - Melati Puspa Nur Fadlilah; Sugito Sugito; Rita Rahmawati (Jurnal Gaussian, 2017)
Customer Service is one form of service facility at PT. Bank X which is directly related with the public as customers. It contains kind of transactions that often caused a queue. To increase public interest in the activities of banking transactions, the facility provider tries to gives satisfaction to the customers who come, so they do not have to wait too long but without make disadvantages to the existing service system. Queueing analysis have been done in order to determine how the service system of Customer Service. Based on the analysis of research data on June, 27th 2016 to July, 1st 2016, a queueing model on Customer Service PT. Bank X is (Poisson/Weibull/3):(FCFS/∞/∞) with the customer arrival rate does not exceed the service rate. In that queueing model, the number of arrivals is Poisson distribution, service time is Weibull distribution and there are three service counters. Queueing discipline that applied is customers will be served were the first comes to the bank, with the system capacity and the calling population of customers is infinite. To provide information as a reference or consideration to the PT. Bank X, then a simulation with the software called Arena has been done to determine the performance of the service system with the addition or subtraction of the number of Customer Service.Keywords: Service, Customer, Bank, Customer Service, Queueing Model, Simulation, Arena.